1992
DOI: 10.1007/bf00338058
|View full text |Cite
|
Sign up to set email alerts
|

The alpha2-adrenergic receptor system in the hypothalamus of the Pekin duck

Abstract: In the present study, we have employed the monoradioiodinated alpha 2-agonist clonidine ([125I]-CLO) to characterize duck hypothalamic alpha 2-adrenoceptors and to localize alpha 2-specific binding sites in the duck brain. To validate the alpha 2-specificity of [125I]-CLO using an enriched duck hypothalamic membrane fraction, a radioreceptor assay was established by altering the membrane protein concentration, time, temperature and ionic milieu of incubation, and in the presence or absence of protease inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
3
0
1
Order By: Relevance
“…The distribution of the a 2 -adrenoceptors functional binding through the chicken brain confirms their functional presence in areas related to the visual system described for other avian species such as the pigeon, quail or duck (Ball et al, 1989;FernandezLopez et al, 1990FernandezLopez et al, , 1997Muller and Gerstberger, 1992) using other methodological approaches. The a 2 -adrenoceptors activation can be observed in hyperpallia and tectum opticum, both related to avian visual pathways (Korzeniewska and Gunturkun, 1990); in the interpeduncular nucleus, related to brightness discrimination retention (Hemmendinger and Moore, 1984); and in the EdingerWestphal nucleus (also known as the accessory oculomotor nucleus), that is the accessory parasympathetic cranial nerve nucleus of the oculomotor nerve.…”
Section: Discussionsupporting
confidence: 66%
“…The distribution of the a 2 -adrenoceptors functional binding through the chicken brain confirms their functional presence in areas related to the visual system described for other avian species such as the pigeon, quail or duck (Ball et al, 1989;FernandezLopez et al, 1990FernandezLopez et al, , 1997Muller and Gerstberger, 1992) using other methodological approaches. The a 2 -adrenoceptors activation can be observed in hyperpallia and tectum opticum, both related to avian visual pathways (Korzeniewska and Gunturkun, 1990); in the interpeduncular nucleus, related to brightness discrimination retention (Hemmendinger and Moore, 1984); and in the EdingerWestphal nucleus (also known as the accessory oculomotor nucleus), that is the accessory parasympathetic cranial nerve nucleus of the oculomotor nerve.…”
Section: Discussionsupporting
confidence: 66%
“…Pretreatment with α 1 -and α 2 -specific antagonists significantly attenuates the ANGII-evoked AVP secretion, possibly because of the blockade of postsynaptic α 1 -and/or α 2 -adrenoceptors, unlike the postulated inhibitory presynaptic α 2 -adrenoceptors in the duck (Stadler et al 1992;Veltmar et al 1992;Thsushima et al 1995). The joint stimulatory action of centrally applied ANGII and norepinephrine on AVT release in the duck, and the co-expression of ANGII, β-and α 2 -adrenoceptors within the PVN indicate the interaction of both neuromodulators in the duck PVN (Gerstberger et al 1984(Gerstberger et al , 1987Müller and Gerstberger 1992).…”
Section: Discussionmentioning
confidence: 91%
“…A high density of catecholaminergic terminals within the PVN, primarily originating in the reticular formation of the brainstem, has been described both for the rat (Dahlström and Fuxe 1965;Sawchenko and Swanson 1981) and Pekin duck (Abel et al 1975;Korf 1984;Müller 1991). Receptor binding studies have demonstrated the presence of various adrenoceptor subtypes in the rat PVN (Rainbow et al 1984;Unnerstall et al 1984;Jones et al 1985) and the expression of α 1 -, α 2 -, and β-adrenoceptors in the duck PVN, with a pattern comparable to that found in the rat Müller and Gerstberger 1992). Intracerebroventricular (i.c.v.…”
Section: Introductionmentioning
confidence: 93%
“…Further mediators could be involved in the possible modulation of paraventricular ANGII receptors in AVT release. Müller and Gerstberger (1992) consider that noradrenaline participates in AVT release at the level of the PVN in birds. On the other hand, Tanaka et al (1985) have suggested that ANGII-sensitive neurons that are found in the SFO and that have efferent projections to the PVN (Lind et al 1984) play a direct role in modulating posterior pituitary secretion.…”
Section: Discussionmentioning
confidence: 99%